Detection of internal defects in CFRP strengthened steel structures using eddy current pulsed thermography. (3rd May 2021) - Xie, Jing; Wu, Changwei; Gao, Lemei; Xu, Changhang; Xu, Yinsheng; Chen, Guoming
Highlights: An NDT method for CFRP strengthened steel structures is proposed based on ECPT. Theoretical, numerical and experimental work is conducted to study the effectiveness of the method. The proposed method shows a promising way to detect various kinds of internal defects. Abstract: This study investigates the effectiveness of eddy current pulsed thermography (ECPT) to detect internal defects in CFRP strengthened steel structures. Various common internal defects of CFRP strengthened steel structures are involved in this study, including delaminations, low-velocity impact damages in CFRP, cracks in steel, and debonding in the CFRP/steel interface. We theoretically analyzed the influence of these defects on the electromagnetic and thermal response of the structures. In order to verify the theoretical results, numerical and experimental investigations are performed on CFRP strengthened steel plates with various kinds of defects. Numerical and experimental results demonstrate that the investigated defects can be inspected by ECPT and indicated as low-temperature regions in the ECPT thermograms. Besides temperature features of thermograms, temperature profile evolutions and temperature evolutions are investigated to further analyze the thermal response on the CFRP surface. Moreover, the efficacy of ECPT in retrieving the shape and size of defects is demonstrated based on the experimental results. In general, theoretical, numerical and experimental results demonstrate that ECPT is effective in inspecting internal defects in CFRP strengthened steel structures, which indicates that ECPT provides a promising way for such a complicated hybrid structure.